The Development of Hybrid Learning in Islamic Religious Education (PAI) - Setyawan, Roby; Sri Murhayati; Zaitun (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to examine the development of the Hybrid Learning model in Islamic Religious Education (PAI) as a solution to the challenges of teaching and learning in the digital era. Using a descriptive qualitative method, the research explores the integration of online and offline learning designed systematically to enhance the effectiveness and quality of PAI instruction. Hybrid learning has the potential to increase student engagement, enrich learning materials, and foster independent learning. Key strategies for successful implementation include the selection of relevant digital media, strengthening the role of teachers, and designing an adaptive curriculum. Thus, Hybrid Learning can serve as an innovative approach to meeting the needs of Islamic education in the modern era.